Pendampingan Implementasi Strategi Pembelajaran Inovatif Berbasis STEM dan Cooperative Script dalam Kurikulum Merdeka bagi Guru Madrasah Ibtidaiyah - Muhammad Feri (Ngarsa: Journal of Dedication Based on Local Wisdom, 2026)
Implementing the Merdeka Curriculum in Madrasah Ibtidaiyah (MI) requires teachers to adopt innovative, student-centered, contextual, and collaborative learning strategies. However, preliminary observations revealed that teachers at MI Al-Manar in Bogor Regency had limited competence in integrating STEM and the Cooperative Script model into Indonesian language instruction. This community service program aimed to enhance teachers' pedagogical competence and develop teaching modules aligned with the principles of the Merdeka Curriculum. The program employed a Participatory Action Research (PAR) approach comprising problem identification, action planning, workshop implementation, mentoring in module development, reflection, and evaluation. Twelve teachers participated in the program. Data were collected through pretest–posttest questionnaires and documentation of mentoring outcomes and analyzed using descriptive quantitative and qualitative methods. The results showed that the average pretest score increased from 56.42 to 82.75 in the posttest, representing an improvement of 26.33 points (46.7%). In addition, participants successfully developed practical Indonesian language-teaching modules that integrate STEM and the Cooperative Script model. The novelty of this program lies in integrating these two approaches through product-oriented workshops and mentoring. The program strengthened teachers' pedagogical competence while providing practical instructional resources to support the effective implementation of the Merdeka Curriculum in Islamic elementary schools. Keywords: Merdeka Curriculum, Innovative Learning, STEM, Cooperative Script, Islamic Elementary School Abstrak: Implementasi Kurikulum Merdeka di Madrasah Ibtidaiyah (MI) menuntut guru untuk menguasai pembelajaran inovatif yang berpusat pada peserta didik, kontekstual, dan kolaboratif. Namun, hasil observasi menunjukkan bahwa guru MI Al-Manar Kabupaten Bogor masih memiliki keterbatasan dalam mengintegrasikan pendekatan STEM dan model Cooperative Script pada mata pelajaran Bahasa Indonesia. Kegiatan pengabdian ini bertujuan untuk meningkatkan kompetensi guru serta menghasilkan modul ajar yang sesuai dengan prinsip Kurikulum Merdeka. Metode yang digunakan adalah Participatory Action Research (PAR) melalui tahapan identifikasi masalah, perencanaan, workshop, pendampingan penyusunan modul ajar, serta refleksi dan evaluasi. Peserta kegiatan berjumlah 12 guru. Data dikumpulkan menggunakan angket pretest–posttest dan dokumentasi hasil pendampingan, kemudian dianalisis secara deskriptif kuantitatif dan kualitatif. Hasil menunjukkan nilai rata-rata pretest meningkat dari 56,42 menjadi 82,75 pada posttest, atau naik sebesar 26,33 poin (46,7%). Selain itu, guru berhasil menyusun modul ajar Bahasa Indonesia berbasis STEM dan Cooperative Script yang relevan dan aplikatif. Kebaruan pengabdian ini terletak pada integrasi kedua pendekatan tersebut melalui workshop dan pendampingan berbasis produk. Program ini berkontribusi dalam meningkatkan kompetensi pedagogik guru sekaligus menyediakan perangkat ajar yang mendukung implementasi Kurikulum Merdeka di madrasah. Kata kunci: Kurikulum Merdeka, pembelajaran inovatif, STEM, Cooperative Script, Madrasah Ibtidaiyah